Kedudukan majelis permusyawaratan rakyat dalam struktur ketatanegaraan Indonesia - Anang Priyanto (Jurnal Civics: Media Kajian Kewarganegaraan)
People's Consultative AssemblY or MPR is often called a state institution in the constitutional structure of the Republic of Indonesia regulated in 1945 and has since established the Assembly of the Republic of Indonesia has undergone a repositioning. The most fundamental repositioning occurred in the reform period, the Assembly which had been before positioned as the highest state institution as the embodiment OJ popular sovereignty became a state institution that has the same position with other state agencies. Even the position of the AssemblY becomes unclear whether as a permanent body or a joint session.